(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
Considering some lessons learnt about criminal liability for HIV exposure and transmission, this paper deals with criminal “reckless” harmful/contagious conducts with fatal outcomes. The main imputation problems might arise, also facing the CoViD-19 scenario, about: (1) the evidence for the causal link to determine whether the defendant effectively caused the event; (2) the distinction between “negligence” and “intent”, and the limits of criminal “recklessness”, according to the Italian Penal Code; (3) the confirmation of the so-called “risk link” between reckless conducts and caused events, concerning the possibly interrupting relevance of victims’ conscious/voluntary exposure to the risk of contagion.